2019
DOI: 10.1055/s-0039-3400252
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biology of Tachykinins in Gonadotropin-Releasing Hormone Secretion

Abstract: The tachykinin family of peptides, composed of the neurokinins A and B (NKA, NKB) and substance P are involved in the central control of gonadotropin-releasing hormone (GnRH) release through a variety of neuronal circuitries that mediate the activation of Kiss1 neurons and the synchronization of their activity within the arcuate nucleus. The major outcome of this role is the precise regulation of the pulsatile pattern of GnRH release. In addition, tachykinins are involved in the maturation of the reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 122 publications
(222 reference statements)
1
8
0
Order By: Relevance
“…The role of tachykinins in regulating reproductive function has been described in several species. Tachykinins (NKA, NKB, and SP) have been shown to significantly stimulate gonadotropin release (in a sex steroiddependent manner in the case of NKA and NKB) [1,27]. The present study extends our knowledge of the role of tachykinins in puberty onset, generation of GnRH pulses, and mounting of the preovulatory LH surge.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The role of tachykinins in regulating reproductive function has been described in several species. Tachykinins (NKA, NKB, and SP) have been shown to significantly stimulate gonadotropin release (in a sex steroiddependent manner in the case of NKA and NKB) [1,27]. The present study extends our knowledge of the role of tachykinins in puberty onset, generation of GnRH pulses, and mounting of the preovulatory LH surge.…”
Section: Discussionsupporting
confidence: 66%
“…Overall, the action of tachykinins on the HPG axis has been documented from early developmental stages, where NKB has been posed with the critical role of serving as a stimulator of kisspeptin release to awaken the reproductive axis, therefore kick-starting puberty onset [1,27,28]. Studies using a single deficiency of tachykinin models (Tac1KO and Tac2KO) have exhibited a delay in puberty onset in males and females, supporting that not only NKB but also NKA/SP have a role in the timing of the pubertal release of kisspeptin/GnRH.…”
Section: Tachykinins Are Required For the Proper Timing Of Puberty Onsetmentioning
confidence: 99%
“…These data point out that, despite the potential redundancy among the TAC pathways, NK2R plays a genuine, specific role in defining specific aspects of LH pulsatility. Of note, previous evidence had demonstrated that, although the stimulatory effects of NKA on GnRH/LH secretion require a preserved kisspeptin signaling (36), Tacr2 is not expressed in Kiss1 (or GnRH) neurons, suggesting a primary site of action of NKA on upstream afferents to Kiss1 neurons (15). These might include Tac1 neurons in the ventromedial hypothalamus (VMH), which express Tacr2, as well as unidentified neurons from the ARC and VMH (36).…”
Section: Discussionmentioning
confidence: 97%
“…To date, most attention in TAC research has focused on the biological effects of SP, NKA (both encoded by a single gene, Tac1 in rodents), and NKB (encoded by Tac2 in rodents), which bind preferentially to the G-proteincoupled receptors NK1R (encoded by Tacr1), NK2R (encoded by Tacr2), and NK3R (encoded by Tacr3), respectively (10,11,13). Notwithstanding this ligand preference, some degree of cross reactivity between TACs and their receptors has been documented (14,15). Thus, while TAC effects on LH release were blunted by central administration of an antagonist for all three receptors, administration of each TAC receptor antagonist alone had no effect on LH secretion in rats (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation